Burma Forest Bulletin No. 17 (Silviculture Series No. 18 Published in 1927). Volumes of Single Trees and Volumes and Number of Trees Per Agre from Data Collected in Teak Plantations in Burma. Also Volumes of Sample Trees of Dipterocarpus Tuber-culatus, Terminalia Tomentosa and Terminalia Pyrifolia - Shirley, G. S. (Indian Forester, 1928)
No abstract